Manufacture of Digftal Distance Measuring Instruments Using Ultrasonic Waves - Untung Firdaus (Institute of Computer Science (IOCS), 2022)
Ultrasonic sensors are widely used in various fields of application such as car alarm systems, automatic door controls, measuring the level of viscosity of liquids, measuring the tensile force on screws and others. In this study, ultrasonic sensors were applied to manufacture digital distance measuring devices that resonate at a frequency of 40 KHz above the threshold of human hearing. Ultrasonic sensors are made of piezoelectric material which has two properties, namely direct piezoelectric properties and reverse piezoelectric properties, then the sensor will change the physical quantity to electronic quantity. The principle of this tool is shooting pulses from the transmitter with the TX sensor until it hits the object to be measured until it returns to the receiver with the RX sensor. By measuring the length of time it takes for the transmitted wave to return to the sensor, then calculates the target distance using the speed of sound in the medium (air), then the conversion value will be obtained in the form of the distance. Object detection by ultrasonic sensors is influenced by several factors such as the characteristics or ability of the sensor system to reach objects, the surface area of ??objects and environmental conditions such as air humidity and temperature. This tool uses a seven/segment display as a display of measured distance values, with changes in distance every 0.01 meters, with the closest detectable measuring distance of 5 cm and the farthest measuring distance of 300 cm. Object detection by ultrasonic sensors is influenced by several factors such as the characteristics or ability of the sensor system to reach objects, the surface area of ??objects and environmental conditions such as air humidity and temperature. This tool uses a seven/segment display as a display of measured distance values, with changes in distance every 0.01 meters, with the closest detectable measuring distance of 5 cm and the farthest measuring distance of 300 cm. Object detection by ultrasonic sensors is influenced by several factors such as the characteristics or ability of the sensor system to reach objects, the surface area of ??objects and environmental conditions such as air humidity and temperature. This tool uses a seven/segment display as a display of measured distance values, with changes in distance every 0.01 meters, with the closest detectable measuring distance of 5 cm and the farthest measuring distance of 300 cm.